Acute Myopericarditis after the Second Dose of mRNA COVID-19 Vaccine Mimicking Acute Coronary Syndrome. (9th August 2022) - Pantsios, Chris; Anyfantakis, Zacharias-Alexandros; Xanthopoulos, Andrew; Leventis, Ioannis; Skoularigkis, Spyridon; Dimos, Apostolos; Bourazana, Angeliki; Papamichalis, Michail; Giamouzis, Grigorios; Triposkiadis, Filippos; Skoularigis, John
Abstract : Myocarditis is a rare adverse event of vaccination. Recently, mRNA vaccines for COVID-19 have been reported to correlate with myocarditis, specifically in adolescents and young men. We report a rare case of a 50-year-old man who presented with symptoms of myocardial infarction 3 days after the second dose of vaccination for COVID-19. Cardiac magnetic resonance (CMR) imaging revealed acute myopericarditis. Clinicians should be aware of that rare side effect of mRNA vaccines for COVID-19 that can affect not only younger recipients but also middle-aged patients presenting with symptoms mimicking acute coronary syndrome.